Publications Received (Academy of Management Review, 1999)
The article lists publications including: “Career Barriers: How People Experience, Overcome and Avoid Failure,” by Manuel London; “The Courage to Teach: Exploring the Inner Landscape of a Teacher's Life,” by Parker J. Palmer; “Entrepreneurship and Productivity,” by Edward E. Williams and James R. Thompson; and “Why So Slow: The Advancement of Women,” by Virginia Valian.